THE VIABILITY TEST OF SAPPAN WOOD (CAESALPINIA SAPPAN L.) ETHANOL EXTRACT IN THE H9C2 CELL LINE - SULISTIYORINI, IFA; SAFITRI, RATU; LESMANA, RONNY; SYAMSUNARNO, MAS RIZKY A. A. (International Journal of Applied Pharmaceutics, 2020)
Objective: In this study, the embryonic rat cardiomyocyte cell line H9C2 was used to investigate the cardiotoxicity effect of sappan wood ethanol extract (SWEE). Methods: Sappan wood was extracted in 96% ethanol and divided into dose concentrations of 2.5, 5, 10, 50, 100, and 150 μg/ml, with deferiprone used as a control. Cell viability was assessed using the PrestoBlue Cell Viability Reagent, according to manufacturer protocols. Results: Microscopic examination showed that the cell viability of H9C2 was preserved by SWEE treatments at a dose of 10 μg/ml and suggested dose concentrations of 50 μg/ml of SWEE. The percentage of viable cells was greater than 95% with a dose concentration of 10 μg/ml of SWEE, but it was significantly reduced with a dose concentration of 50 μg/ml of SWEE (p<0.05). Conclusion: The optimal dose concentration of SWEE to reach 95% cell viability was 10 μg/ml.